Analisis Kinerja Perbankan Syariah (Implementasi Maqasid al-Syari‘ah Index di PT BPRS Jabal Nur) - Nurul Fatma Hasan (Institut Ilmu Keislaman Annuqayah, 2017)
This study aims to analyze the implementation of maqa>sid al-syari>‘ah index in measuring the performance of PT BPRS Jabal Nur and analyze the performance of PT BPRS Jabal Nur based on maqa>sid al-syari>‘ah index. This research includes in the type of descriptive quantitative research, the data used is secondary data, derived from the annual report of PT BPRS Jabal Nur in 2010-2014. The results show that maqa>sid al-syari>‘ah index can be implemented to measure the performance of PT BPRS Jabal Nur. However PT BPRS Jabal Nur does not implement all the indicators mentioned in maqa>sid al-syari>‘ah index. PT BPRS Jabal Nur only runs education grant & training indicators, publicity, fair return, funcional distribution, interest free income, profit ratios, and personal income. PT BPRS Jabal Nur does not run research and investment indicators in real sector. The obstacles in implementing maqa>sid al-syari>‘ah index is sourced from the factor of unavailability data. The value of maqa>sid al-syari>‘ah that achieved by PT BPRS Jabal Nur is fluctuating. In 2010, the value of maqa>sid al-syari>‘ah index of PT BPRS Jabal Nur reached 0.28301, in 2011 reached 0.30293, in 2012 reached 0.31376, in 2013 reached 0.30309, and in 2014 reached 0.30255. The average value maqa>sid al-syari>‘ah index of PT BPRS Jabal Nur in 2010-2014 is 0.3010.